2022
DOI: 10.3389/fnut.2022.809983
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Probiotic Research in Athletic and Physically Active Populations: Guidance for Future Randomized Controlled Trials

Abstract: Probiotic supplementation, traditionally used for the prevention or treatment of a variety of disease indications, is now recognized in a variety of population groups including athletes and those physically active for improving general health and performance. However, experimental and clinical trials with probiotics commonly suffer from design flaws and different outcome measures, making comparison and synthesis of conclusions difficult. Here we review current randomized controlled trials (RCTs) using probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 137 publications
0
16
0
Order By: Relevance
“…While mechanistic considerations for postbiotics have been proposed by Ma and colleagues [ 73 ], no research to date has systematically examined the extent to which any of these mechanisms, or any others, may help to explain the efficacy surrounding postbiotic use in athletes. Much like the challenges involving probiotic use in sports, early findings have suggested that strain specificity with postbiotics will continue to be a central issue, while study design considerations including dosing amount and duration should be critical factors considered in future research [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…While mechanistic considerations for postbiotics have been proposed by Ma and colleagues [ 73 ], no research to date has systematically examined the extent to which any of these mechanisms, or any others, may help to explain the efficacy surrounding postbiotic use in athletes. Much like the challenges involving probiotic use in sports, early findings have suggested that strain specificity with postbiotics will continue to be a central issue, while study design considerations including dosing amount and duration should be critical factors considered in future research [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, more high-quality, large, randomized controlled trials are needed. These studies should incorporate best practice methodologies [ [72] , [73] , [74] ], include diagnosis of GTI, and (when possible) identify specific pathogens causing infection. Within that context, confirmatory studies of specific probiotic strains and mixtures, prebiotic types, and synbiotic formulations will be especially critical to generate the evidence needed to tailor recommendations for particular interventions (i.e., specific probiotic strains or mixtures or prebiotic types) to specific populations and environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participants were excluded if they had a history of antibiotics or consumed probiotics in the 2 months before enrollment in the study. If a participant had recently consumed probiotics, an 8-wk washout period (22) was required before enrollment in the study to ensure the potential effects of the probiotics were eliminated. However, no participant reported consuming probiotics within the previous 3 months of their participation in the study.…”
Section: Methodsmentioning
confidence: 99%